18S rDNA phylogeny of Pseudo-nitzschia (Bacillariophyceae) inferred from sequence-structure information - Lim, H.C.; Teng, S.T.; Lim, P.T.; Wolf, M.; Leaw, CP (Allen Press Publishing Services, 2016)
We explored the 18S rDNA sequences of Pseudo-nitzschia and its close relatives, together with their individual secondary structure information to reconstruct phylogenies. Forty-eight taxa classified in the Bacillariaceae and Achnanthaceae were analyzed by character-based (maximum parsimony and maximum likelihood) and distance-based (neighbour-joining) methods. Three raphid diatoms from the Eunotiaceae were used as out-groups. The sequencestructure alignment was generated by 4SALE (i.e. a one-letter encoded alignment that contained the individual secondary structure information) and applied to the character-based phylogeny reconstruction. All analyses highly support Pseudonitzschia + Fragilariopsis as monophyletic. The Pseudo-nitzschia/Fragilariopsis clade is further divided into three subclades. One clade comprises members in the P. seriata and P. americana complexes and species of Fragilariopsis; the second and third clades constitute members in P. pseudodelicatissima and P. delicatissima complexes. Among all analyses, the distance-based method yielded a more highly resolved phylogenetic framework for the Pseudo-nitzschia/Fragilariopsis clade than did the character-based analyses. Other than those currently known genetic markers, 18S rDNA was also useful in exploring the intrageneric relationships.